Population dynamics, biology of mealybug Phenacoccus solenopsis (Tinsley) and its natural enemies in Vadodara, Gujarat - Singh, Anita; Kumar, Dolly (Recent Research in Science and Technology, 2013)
The population dynamics study of Phenacoccus solenopsis (Tinsley), a serious pest in Vadodara, India, were conducted during 2008-2011. The results show that the mealybug population is higher in the month of October on cotton (Gossypium hirsutum L.) and Okra (Abelmaschus esculentus L.). Whereas maximum population of mealybug were seen in the month of February on Tomato (Lycopersicon esculentum L.) and Potato (Solanum tuberosum L.) host plants. The correlation of mealybug population was done with abiotic and biotic parameters. The mealybug population was showing positive correlation with higher temperature, population of predator and parasitoids whereas negative correlation with lower temperature and humidity. Further the biology of the Phenacoccus solenopsis (Tinsley) was studied on Hibiscus rosa-sinensis (L.) under the laboratory conditions. The results on different biological parameters showed that the fecundity rate of female ranged from 300 to 750 which increased its survival rate. The longevity of female was higher (24.44±2.329 days) than male (1.960±0.8406 days). Hence, the information contained in this paper lead to the identification of proper management practises during effective reproductive period for Phenacoccus solenopsis management.